The Role of Artificial Intelligence and Remote Sensing Technologies in Forest Ecosystems and Their Importance in Determining Carbon Capture Potential - Güler, Sümeyye (Prensip Publishing, 2024)
Climate change and global warming are among the most pressing environmental issues requiring urgent and adequate global action to protect future generations worldwide. One of the key approaches used to reduce CO2 emissions and mitigate the worst effects of climate change is carbon capture technologies. Carbon capture technologies have the potential to capture carbon from the atmosphere and convert it into fuels that can be used in environmentally friendly energy production. Innovative technologies can enhance carbon capture potential, which can play a significant role in combating climate change. Better understanding of mechanisms for capturing, storing, and releasing carbon from the atmosphere allows for more accurate assessments of carbon capture potentials. Scientists, industries, and policymakers are making significant efforts to explore new technologies to reduce greenhouse gas emissions and achieve net-zero emission goals. Development of new technologies involves complex processes and requires a digital system to optimize big data forecasting and reduce production time. Mathematical and statistical approaches play a crucial role in solving research problems, providing fast results and cost-effective tools for predicting large datasets. Effective policies for carbon capture and international cooperation can enhance carbon capture potential. New policies and collaboration models can incentivize investment in carbon capture projects, thereby increasing their potential. These new approaches can be used to better understand carbon capture potential and develop effective solutions to combat climate change. However, research in this field is still ongoing, and further research and development will be needed in the future.
Keywords: 9. Industry and infrastructure; 13. Climate action; 11. Sustainability; 15. Life on land; 7. Clean energy; 12. Responsible consumption